2020
DOI: 10.1002/admi.202000887
|View full text |Cite
|
Sign up to set email alerts
|

Toward BaSi2/Si Heterojunction Thin‐Film Solar Cells: Insights into Heterointerface Investigation, Barium Depletion, and Silicide‐Mediated Silicon Crystallization

Abstract: for a conveniently synthesized material with minimal toxicity and adequate availability, has triggered a research focus toward barium silicide (BaSi 2). This is regarded as a low-cost alternative to conventional absorber materials. [1,2] The semiconducting BaSi 2 is stable in the ambient condition, [3] and exhibits an orthorhombic crystal structure. The Si atom is covalently bound with three neighboring Si atoms forming the characteristic tetrahedron [Si 4 ] 4− , then with Ba 2+. [4,5] Besides the essentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Subsequently, the crystalline orientation shifted further with a higher activation energy from annealing at 900 • C. The β (202)/(220) evolved dramatically, causing a superposition between itself and Si(111). At the same time, several peaks of β (400), β (331), β (422), and β (333) appeared at 34.72, 45.20, 49.80, and 58.90 • , respectively [22,29]. When annealing further, the sample at the phase above the ideal Si concentration of the D03 structure can retain the phase from the boundary of 26% at RT to 31% at 1200 • C, even when an absurd phase transition occurs [5].…”
Section: Xrd Results Of Fe 3 Si Filmsmentioning
confidence: 91%
“…Subsequently, the crystalline orientation shifted further with a higher activation energy from annealing at 900 • C. The β (202)/(220) evolved dramatically, causing a superposition between itself and Si(111). At the same time, several peaks of β (400), β (331), β (422), and β (333) appeared at 34.72, 45.20, 49.80, and 58.90 • , respectively [22,29]. When annealing further, the sample at the phase above the ideal Si concentration of the D03 structure can retain the phase from the boundary of 26% at RT to 31% at 1200 • C, even when an absurd phase transition occurs [5].…”
Section: Xrd Results Of Fe 3 Si Filmsmentioning
confidence: 91%
“…[15,21] In this review, we focus on the recent progress of BaSi 2 to bridge the gap between the present status and that described in previous review articles. [14,15] Great progress has especially been made in thinfilm deposition techniques [22][23][24][25][26][27][28][29][30][31] and understanding the surface structure of BaSi 2 epitaxial films, [32] the reactions at the air/BaSi 2 and BaSi 2 /Si interfaces during post annealing, [33][34][35][36][37] and understanding the importance of satisfying the stoichiometry. [38,39] By positron annihilation spectroscopy, [39] it has been revealed that the electron concentration increases to %10 18 cm À3 with increasing vacancy-type defects [38] when the Ba/Si atomic ratio is far from the stoichiometric ratio.…”
Section: Introductionmentioning
confidence: 99%